Changes of lipoprotein(a) levels with endogenous steroid hormones. (8th November 2021) - Tessitore, Elena; Dobretz, Kevin; Dhayat, Nasser Abdalla; Kern, Ilse; Ponte, Belen; Pruijm, Menno; Ackermann, Daniel; Estoppey, Sandrine; Burnier, Michel; Martin, Pierre‐Yves; Vogt, Bruno; Vuilleumier, Nicolas; et al.
Abstract: Background: Lipoprotein(a) [Lp(a)] is an LDL‐like molecule that is likely causal for cardiovascular events and Lp(a) variability has been shown to be mostly of genetic origin. Exogenous hormones (hormone replacement therapy) seem to influence Lp(a) levels, but the impact of endogenous hormone levels on Lp(a) is still unknown. The aim of the study was to assess the effect of endogenous steroid hormone metabolites on Lp(a). Methods: Lipoprotein(a) levels were measured in 1, 021 participants from the Swiss Kidney Project on Genes in Hypertension, a family‐based, multicentre, population‐based prospective cohort study. Endogenous levels of 28 steroid hormone precursors were measured in 24‐h urine collections from 883 individuals. Of the participants with Lp(a) data, 1, 011 participants had also genotypes available. Results: The participants had an average age of 51 years and 53% were female. Median Lp(a) levels were 62 mg/L, and the 90 th percentile was 616 mg/L. The prevalence of a Lp(a) elevation ≥700 mg/L was 3.2%. Forty‐three per cent of Lp(a) variability was explained respectively by: age (2%, p  < .001), LDL‐C (1%, p  = .001), and two SNPs (39%, p value<2⋅10 −16 ). Of the 28 endogenous steroid hormones assessed, androstenetriol, androsterone, 16α‐OH‐DHEA and estriol were nominatively associated with serum Lp(a) levels in univariable analyses and explained 0.4%–1% of Lp(a) variability, but none of them reached significance in multivariable models. Conclusions: In this contemporary population‐based study, the prevalence of a Lp(a) elevation ≥700 mg/L was 3.2%. The effect of endogenous steroid hormone levels of Lp(a) variability was small at best, suggesting a negligible impact on the wide range of Lp(a) variability.